Research for the application of frequency modulation Interferometer to measure the deformation of aluminum alloy when temperature changes in optical devices - Hoàng Anh Tú; Vu, Thanh Tung; Phạm Đức Tuân; Lê Văn Văn (Journal of Military Science and Technology, 2024)
This article presents the theoretical foundation and application of a new method to measure the deformation of aluminum alloys due to temperature changes using a frequency-modulated interferometer (FMI). Aluminum alloys are important components, often used in manufacturing and mounting lenses for optical devices. When the temperature changes, the thickness and axial dimensions change according to the thermal expansion coefficient of the material, causing defocus that reduces the image quality of the optical device. Because the exact material used is often unknown in practice, it becomes difficult to precisely calculate the change caused by the thermal expansion coefficient. Therefore, a method to directly measure the material’s actual deformation caused by temperature change is necessary to implement a temperature compensation solution from the design stage. The proposed FMI offers a simple structure and a new signal processing technique that can measure the small deformations of aluminum alloy with high accuracy under varying temperatures.